Marx, Keynes e Minsky: a supremacia das finanças no capitalismo contemporâneo - Camargo, Leonardo de Carvalho (2009)
In the last three decades of the twentieth century and the first of the internal forces of the capitalist system have changed in such a way, that show has achieved a new kind of capitalism that currently in force. It is a type of financial capitalism - with the globalization of high finance as its ultimate expression. This new corporate arrangement is characterized by chronic instability that leads to many problems on a global scale. From which highlights the supremacy of the financial sphere on the production. This supremacy is a destabilizing component of investment, the financing of productive activities, employment and income. Moreover, dismantled the National States and its ability to intervene in order to bring discipline and order to the system. National states were also affected in their capacity to create and effectively implement policies aiming at full employment and better generation and distribution of income and wealth. From the middle of last century, historical and structural forces emerged and were expanded in contemporary capitalism. This junction with the structural history has made possible the dominance of finance mainly through their higher aspect: the financial globalization (Chapter I). The effort of this dissertation focuses on the argument that the supremacy of finance is a characteristic inherent in the modus operandi of capitalism and that if the system does not suffer the imposition of rules and discipline, crises and instability are increasing, and entail more harm to society as a whole. To consolidate this argument, the study draws on the analysis of three thinkers who, in their conceptions and theoretical formulations, pointed to a clear and endogenous tendency in capitalism for the supremacy of finance. Marx's analysis of the actual movements of capital and its developments culminating in the absolute form of wealth expressed by the fictitious capital (Chapter II); Keynes with his revolutionary interpretation of an economy that is essentially monetary and in which the agents, faced with the expectations arising from an uncertain future, opt for more liquid assets, thus depressing the investment and productive activity (Chapter III), and Minsky with his hypothesis of financial fragility, which is a result of a complex economy that needs funding for the growth in a world characterized by unpredictability of economic activity over time (Chapter IV). Are the theoretical and analytical here used to undergird and support the argument that the supremacy of finance is an inherent feature of the development of the capitalist system of production.